Efficiency and usability of a modified pegboard incorporating computerized technology for upper limb rehabilitation in patients with stroke. Issue 4 (19th May 2023) - Ham, Yeajin; Shin, Joon-Ho
ABSTRACT: Background: Traditionally, a pegboard has been commonly used as a useful training and assessment tool for patients with stroke. However, training using pegboards could be monotonous and may discourage motivation in patients with stroke, as it requires only repetitive movements without feedback. Objectives: We aimed to demonstrate the efficiency and usability of a novel rehabilitation instrument (Rapael Smart Pegboard; SP), which integrates computerized technology into a traditional pegboard. Methods: This single-center study with a single-group pre–post design included 19 patients with hemiplegic stroke (11 outpatients and 8 inpatients). The patients received 20 SP training sessions (30 minutes per session, 5 days per week, over 4 weeks) according to their ability and status without any therapist intervention. The primary outcome was changes in the Fugl–Meyer assessment of upper extremity (FMA), and the secondary outcomes were changes in the Box and Block test and Jebsen–Taylor Hand Function test (JHFT). Additionally, usability assessment was performed. Results: All outcome measurements except JHFT-gross score showed significant improvements with SP training. The significant improvements in these outcomes were consistently found in the outpatient group; however, the inpatient group failed to show improvement in the distal part of FMA, total JHFT score, and time. The usability test showed high satisfaction with 4.9 out of 5 points. Conclusions: The SP is an effective and feasible instrument for upper limb rehabilitation. Moreover, the SP can be used as a self-training tool without the assistance of a health care practitioner.